Do board characteristics matter for growth firms? Evidence from China - Qiuwei Li; Wei Zhou; Hui Zhou; Jiaxuan Chen (Journal of Risk and Financial Management, 2021)
Previous research on the effect of board characteristics mostly examines established firms. This raises the question of whether the findings from the board characteristics literature are applicable to rapidly growing enterprises, as their corporate governance landscape can be very different from that in large, mature companies. Our paper extends the corporate governance literature by investigating the performance implications of board characteristics in startups using a unique set of firms: 121 startups operating in the information technology industry listed on the Growth Enterprise Market (GEM) in China. Using a firm performance indicator constructed through the factor analysis method, we find significant correlations between firm performance and board size, age structure, board meeting frequency, and board ownership of shares. Our findings contribute to the corporate governance literature by shedding new light on the performance implications of board characteristics for startups operating in fast-paced industries.
Keywords: 330; corporate governance; board for startups; emerging markets